Strategies for Teaching English as a Foreign Language (EFL) to Senior High School: A Systematic Literature Review - Afriyan, Agil Putri (UIN Imam Bonjol Padang, 2024)
Learning English has begun to be implemented from junior high to senior high school. The purpose of this article is to outline some effective strategies that are often used by teachers of English as a foreign language (EFL) for students in senior high school. The method used in describing strategies for teaching English as a Foreign Language (EFL) to high school students is to refer to a literature review study. The results of this study found several strategies that can be used by teachers in learning English for high school students, including memory strategies, cognitive strategies, compensatory strategies, metacognitive strategies, affective strategies, and social strategies. The implications of this paper can be useful in the world of education, especially for teachers. Various findings in this paper can be a reference for teachers in developing English learning strategies to make it easier for students to learn.